2021
DOI: 10.3390/cryst11101214
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Tungstate Doped with Rare Earth Ions Synthesized at Low Temperatures for Photoactive Composite and Anti-Counterfeiting Applications

Abstract: A precursor was prepared using a co-precipitation method to synthesize crystalline calcium tungstate. The prepared precursor was dried in an oven at 80 °C for 18 h. The dried powders, prepared without a heat treatment process, were observed in XRD analysis to be a crystalline CaWO4 phase, confirming that the synthesis of crystalline CaWO4 is possible even at low temperature. To use this crystalline CaWO4 as a light emitting material, rare earth ions were added when preparing the precursor. The CaWO4 powders do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The PL spectra, where the peak has been observed at 262 nm and is diffused over the 210–350 nm range, is affected by the PL wavelength of 545 nm. Figure 15 displays the Tb 3+ emission and excitation spectra [29]. A peak in the near UV part of the spectra at 316 nm identifies fluorescent light materials as fluorescent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PL spectra, where the peak has been observed at 262 nm and is diffused over the 210–350 nm range, is affected by the PL wavelength of 545 nm. Figure 15 displays the Tb 3+ emission and excitation spectra [29]. A peak in the near UV part of the spectra at 316 nm identifies fluorescent light materials as fluorescent.…”
Section: Resultsmentioning
confidence: 99%
“…The Tb 3+ : MgLa 2 V 2 O 9 powder phosphors are promising candidates for application in fluorescent lights because of their green emission at 545 nm, which results from an excitation wavelength of 316 nm. It has been shown that magnetic or electric dipole interactions account for the majority of the luminescence seen during transitions between 4f levels [28][29][30][31].…”
Section: Pl Studiesmentioning
confidence: 99%
“…The PL spectrum (green line) was observed for the excitation wavelength 287 nm, stemming from Tb-O CTB [31]. The emission spectra contain five peaks centered at 487, 544, 585, 619, and 649 nm wavelengths, corresponding to the 5 D 4 → 7 F 6 , 5 D 4 → 7 F 5 , 5 D 4 → 7 F 4 , 5 D 4 → 7 F 3 , and 5 D 4 → 7 F 2 transitions [32]. In addition, among the above five components of emission spectra, the intensity of the green emission spectrum due to the 5 D 4 → 7 F 5 (544 nm) magnetic dipole transition was the strongest, and this emission intensity was the strongest due to the 5 D 4 → 7 F 6 (487 nm) electric dipole transition of the Tb 3+ ion.…”
Section: Reviewmentioning
confidence: 99%
“…[27][28][29] The special class of tungstic acid hosts with scheelite crystal structure CaWO 4 with general formula AWO 4 (A = Ca, Sr, Ba, Pb, and Cd) are intriguing in several fields, such as photoluminescence, 30 scintillators, 31 temperature sensing, 32 and catalyst 33 due to their excellent chemical stability and structural characteristics. 34,35 To date, many synthetic strategies have been adapted to obtain distinct chemical activity and shapes of CaWO 4 , including hydrothermal method, 36 the reverse-micelle method, 37 the solid-state reaction, 38 and coprecipitation methods. 39 Among all these synthetic methods ultrasound technique attains consideration being cost effective, high purities, and rapid reaction rate method.…”
Section: Introductionmentioning
confidence: 99%